Research methods in law / edited by Dawn Watkins and Mandy Burton. - Watkins, Dawn. (Dawn Elizabeth); Burton, Mandy (Routledge, 2026)
Designed for use by post-graduate students in law and legal studies this text provides a useful and critically rigorous introduction to the different research methodologies available to the student. It will give students who are setting out on a project or dissertation a firm grounding on which they can base their research.